Attitude of Farmers Toward National Horticulture Mission in Haryana - Kaur, Bas; Chander, Subhash; Baloda, Satpal; Godara, Ashok Kumar; Boora, Sahil; Manisha, (Indian Journal of Extension Education, 2022)
The majority of people in India are dependent directly or indirectly on agricultural sector, which is the country’s largest economic sector. In 2005–06, the Indian government introduced the National Horticulture Mission, a program for the comprehensive development of horticulture, in recognition of the incredible potential of horticulture to promote the expansion of Indian agriculture. The present study was undertaken in the year 2022 to assess the attitude of beneficiary’s farmers towards National Horticulture Mission in Sirsa and Karnal districts of Haryana. A total of 120 farmers were personally interviewed for the purpose of the study and revealed that 43.33 per cent of the respondents had a favourable attitude towards NHM. The type of family, size of horticultural land holding and their socio-economic status, level of education, size of land holding, annual income from horticulture crops, annual family income, mass media exposure had significant association with attitude towards NHM. Establishment of proper cold storage facilities for perishable horticultural crops and more efficient system for diffusion of information to the farmers so that they can adopt new practice efficiently is recommended.
Keywords: Attitude; NHM; Association; Farmers; Agriculture